2009
DOI: 10.1073/pnas.0900713106
|View full text |Cite
|
Sign up to set email alerts
|

Shear thinning in deeply supercooled melts

Abstract: We compute, on a molecular basis, the viscosity of a deeply supercooled liquid at high shear rates. The viscosity is shown to decrease at growing shear rates, owing to an increase in the structural relaxation rate as caused by the shear. The onset of this nonNewtonian behavior is predicted to occur universally at a shear rate significantly lower than the typical structural relaxation rate, by approximately two orders of magnitude. This results from a large size-up to several hundred atoms-of the cooperative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
(70 reference statements)
1
27
2
Order By: Relevance
“…Our findings challenge the traditional, and universal, view of the non‐Newtonian onset [ Vidal Russell and Israeloff , 2000; Berthier et al , 2005; Lubchenko , 2009] where this onset is attributed to cooperative structural rearrangement. Heterogeneous distribution of network modifiers (clustering) in silicate melts/liquids might promote stress localization and create structural non‐Newtonian behavior.…”
Section: Discussioncontrasting
confidence: 81%
“…Our findings challenge the traditional, and universal, view of the non‐Newtonian onset [ Vidal Russell and Israeloff , 2000; Berthier et al , 2005; Lubchenko , 2009] where this onset is attributed to cooperative structural rearrangement. Heterogeneous distribution of network modifiers (clustering) in silicate melts/liquids might promote stress localization and create structural non‐Newtonian behavior.…”
Section: Discussioncontrasting
confidence: 81%
“…The resulting additional enhancement of reconfiguration speed is a facilitation or mode coupling effect. Lubchenko has shown that this effect [that would be contained in a more complete RFOT theory including mode coupling effects (36)] does a good job describing the crossover to steady state nonlinear rheology (37). Similar effects have been studied in mode coupling treatments of dense colloid rheology (38,39).…”
mentioning
confidence: 86%
“…L iquids displaying slow dynamics, such as glass-forming liquids, exhibit striking nonlinear behavior known as shear thinning if subjected to sufficiently strong shear and the behavior is characterized by a power-law decrease of the viscosity η with increasing shear rateγ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Shear thinning is a process relied on heavily for, for example, industrial purposes such as lubrication.…”
mentioning
confidence: 99%